2014
DOI: 10.1002/ece3.1191
|View full text |Cite
|
Sign up to set email alerts
|

Changes in pollinator fauna affect altitudinal variation of floral size in a bumblebee‐pollinated herb

Abstract: Geographic trait variations are often caused by locally different selection regimes. As a steep environmental cline along altitude strongly influences adaptive traits, mountain ecosystems are ideal for exploring adaptive differentiation over short distances. We investigated altitudinal floral size variation of Campanula punctata var. hondoensis in 12 populations in three mountain regions of central Japan to test whether the altitudinal floral size variation was correlated with the size of the local bumblebee p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 65 publications
(107 reference statements)
4
55
0
Order By: Relevance
“…Previous studies that have investigated flower size variations along an altitudinal gradient in mountainous environments have reported corresponding altitudinal variations in, for example, pollinator species composition and nectar robbing frequency (Hattori et al , 2015Nagano et al 2014;Kuriya et al 2015;Zhao & Wang 2015). In this study, we showed that the pattern of flower size variation along an altitudinal gradient differed between two Impatiens species growing in similar habitats.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…Previous studies that have investigated flower size variations along an altitudinal gradient in mountainous environments have reported corresponding altitudinal variations in, for example, pollinator species composition and nectar robbing frequency (Hattori et al , 2015Nagano et al 2014;Kuriya et al 2015;Zhao & Wang 2015). In this study, we showed that the pattern of flower size variation along an altitudinal gradient differed between two Impatiens species growing in similar habitats.…”
Section: Discussionsupporting
confidence: 50%
“…air temperature), or by an altitude-related pollen limitation (Cosacov et al 2008), than by size-matching between flower and pollinator, because the pollinator species composition in central Japan seems to be similar, regardless of time or place. Various environmental factors such as air temperature and pollinator abundance change along an altitudinal gradient (Körner 1999;Nagano et al 2014;Kuriya et al 2015). These environmental factors can affect flower size variation along the gradient (Galen 2000;Knight et al 2005;Parachnowitsch & Kessler 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the species composition of bumblebee populations varies among regions [17]- [19] [21], the floral traits of bumblebee-pollinated plants are expected to vary among regions. In fact, a number of studies have presented evidence from several plant species supporting this expectation [14] [22]- [24]. These studies focus on the interaction between summer-flowering plants and bumblebee workers in summer [25]; the influence of bumblebee queens, which are active in spring, on floral trait variation in spring-flowering plants has less been studied (but see [26]).…”
Section: Introductionmentioning
confidence: 99%